2012
DOI: 10.1002/pen.23284
|View full text |Cite
|
Sign up to set email alerts
|

Environmental stress cracking: A review

Abstract: Environmental stress failure of polymers (specifically glassy thermoplastics) is a major failure mode in application end use. The environmental stress failure discussion will primarily be limited to non‐reactive environments. Crystalline polymers and even lightly crosslinked polymers can exhibit similar failure to glassy polymers but often require a much higher external applied stress. The mechanisms of environmental stress cracking proposed in the literature will be discussed in detail along with testing meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 114 publications
(112 reference statements)
2
57
0
2
Order By: Relevance
“…For automotive applications, blends have been formulated with high T g polymers (PC, PPO) with crystalline polymers (PBT, PA 66) (Robeson 2007). As applications of amorphous polymers expand in adverse environments, newer commercial blends will be developed, and the reader is referred to the recent review by Robeson (2013). This effort is likely to be aided by computational methods that have been developed in the science and technology of polymer blends.…”
Section: Discussionmentioning
confidence: 98%
“…For automotive applications, blends have been formulated with high T g polymers (PC, PPO) with crystalline polymers (PBT, PA 66) (Robeson 2007). As applications of amorphous polymers expand in adverse environments, newer commercial blends will be developed, and the reader is referred to the recent review by Robeson (2013). This effort is likely to be aided by computational methods that have been developed in the science and technology of polymer blends.…”
Section: Discussionmentioning
confidence: 98%
“…Brown 12 studied the theory of the ESC of PE and proved that ESCR would be increased by increasing molecular weight. Robeson 13 pointed out when PE is exposed some chemical substances like alcohols, soaps, fatty acids under multidirectional stresses, it fails because of cracking. They also pointed out that a better cracking resistance could be achieved by choosing suitable high molecular weight resin or through blending polyethylene with polyisobutylene.…”
mentioning
confidence: 99%
“…[35][36][37][38][39] It has been shown that brous reinforcement shows a greater ability to resist crack propagation than particulate reinforcement. [40][41][42][43][44] 3.1 Polymers reinforced with conventional and natural bres Conventional bres or synthetic bres such as carbon bre, glass bre, Aramid and Kevlar are widely used in various engineering applications. [45][46][47][48][49][50][51] High stiffness and excellent strength properties are two important factors that make the applications of these bres favourable.…”
Section: Fibre and Particle Reinforcementmentioning
confidence: 99%